PARTITIONING OF PLATINUM-GROUP ELEMENTS (OS, IR, RU, PT, PD) AND GOLD BETWEEN SULFIDE LIQUID AND BASALT MELT - Fleet M.E.; Crocket J.H.; Stone W.E. (My University, 1996)
New measurements on partitioning of platinum-group elements (PGE) Os, Ir, Ru, Pt, Pd, and Au between (Fe,Ni)-sulfide liquid and basaltic melt using low pressure, sealed silica glass tube, and controlled atmosphere methods at 1200–1250°C show an extremely wide variation, which spans much of the range reported in the literature. In spite of their geochemical coherence in natural high-temperature assemblages, PGE-Au apparently behave as seven different metals in individual laboratory experiments with silicate melts. Sulfide/silicate partition coefficients, D, generally increase with run time, in a manner consistent with either serial change in chemical state of the metals in the silicate melt or passivation of alloy phases. Ruthenium is the only metal presently investigated that exhibits reversible behaviour. Summary partition coefficients for the lowest PGE contents investigated under reducing conditions and low Ni contents remain unchanged, except for the addition of a value of (4.4 ± 2.4) × 10^3 for Ru. Absence of interference from the nugget effect and homogeneity and equilibration of silicate melt in the earlier experiments is demonstrated by new measurements on Ir in different grain-size fractions of glass. An additional set of partition coefficients for 37 mol% NiS and 100–1000 ppm PGE in the sulfide is: D(Os) = (30 ± 6) × 10^3, D(Ir) = (26 ± 11) × 10^3, D(Ru) = (6.4 ± 2.1) × 10^3, D(Pt) = (10 ± 4) × 10^3, and D(Pd) = (17 ± 7) × 10^3.